ANALYSIS AND ASSESSMENT OF FINANCIAL AND BUSINESS ACTIVITIES TO MINIMIZE TAX RISKS OF COMPANIES - E. V. Lyuter (Real Economics Publishing House, 2016)
Below is the original author's approach to the companies' tax risks valuation based on the comparison of the tax and financial statements. Algorithm of the tax risks identification based on the criteria settled by the note of the Federal Tax Authority of Russian Federation from 17.07.2013 №АС-4-2/12722 "About tax authorities committees operation on legalisation of the tax base" is described. Model of the companies classification by tax risks based on the tax burden and specific cash flow is provided.